Exploring New Patterns Of Interaction During Conflict Among Married Individuals In Malaysia - Mohd. Hasim, Marshina Juliza; Mustafa, Hasrina; Hashim, Nor Hazlina (2015)
This study examines the patterns of interaction during conflict among married individuals in Malaysia. Sixty married individuals in Malaysia responded to an openended questionnaire about how they interact with their spouse during conflict situation. Result showed the existence of constructive, destructive and avoidance patterns of interaction during conflict which reflect similarity with conflict interaction in western society. These three patterns are viewed to be more specific and in accordance to the context of Malaysian society